Chronic restraint stress induces gastrointestinal function alternation: A potential role of the ArhGEF18-RhoA/Rho signaling pathway in the brain–gut axis under stress - Xiaohua Ma; Hao Li; Wenjuan Wang; Zhigang Miao (Stress and Brain, 2022)
Depression is one of the common psychiatric diseases worldwide. Previous studies showed that chronic stress could increase defecation and inhibit weight gain; however, the effects of chronic stress on gastrointestinal peristalsis had not been clarified. To study the mechanisms of depression, chronic restraint stress (CRS) is widely used as a traditional depressive animal model. In this study, we investigate the effects of CRS on gastric emptying and intestinal propulsion in mice. Our results showed that the mice exhibited obvious depression-like behaviors 4 weeks after CRS. Compared with the control group, gastric emptying and intestinal propulsion were significantly decreased in the CRS group. Further, we examined the expression of ArhGEF18, a Rho-specific guanine nucleotide exchanging factor, which was significantly reduced in the gut in the CRS group. Therefore, CRS caused depressive behaviors and abnormal gastrointestinal function. The ArhGEF18-RhoA/Rho signaling pathway may be a potential mediator in the brain–gut axis under stress.